The relationship between employee empowerment and organizational commitment at Majlis Perbandaran Dungun,Terengganu / Nur Adlyn Soffiya Mohamad Hafaz - Mohamad Hafaz, Nur Adlyn Soffiya (Faculty of Business and Management, 2019)
This study focuses on Majlis Perbandaran Dungun, Terengganu. This study was conducted to distinguish the relationship between employee empowerment and organizational commitment at Majlis Perbandaran Dungun (MPD). The scope of the study involves the time and money spent, materials, techniques and the number of personnel needed for this research to be completed. This method that has been used in this research is descriptive correlative. The sample size taken in the organization are 108 respondents and the number of populations are 150 as stated in the sample size for the given population by Krejcie and Morgan (2006). The sampling technique used in this research is simple random sampling. The researcher chooses this sampling due to the ease of use and its accurate representation of the larger population. It was totally free from bias and prejudice and very easy to assess the sampling error in this method. From the statistic it shows that the level of empowerment and the level of commitment among employees was high. The research findings can be concluded that there is positive relationship between employee empowerment and organizational commitment.